Possible experience : understanding Kant's Critique of pure reason - Collins, Arthur W. (1999)
This revisionist exposition of Kant's "Critique of Pure Reason" addresses the themes and passages in the text which seem to require an idealist thesis and shows how they may be better understood without ascribing any idealist philosophy to Kant
1. Kant and the Cartesian Philosophy of Mind -- 2. Subjectivism versus Idealism -- 3. Idealism and Transcendental Idealism -- 4. Are Things-in-Themselves Noumena? -- 5. The Concept of Representation -- 6. "Space Is in Us" -- 7. Outer Causes of Perception -- 8. Kant Not a Foundationalist -- 9. The "How-Possible" Questions -- 10. The "Clue" for Finding the Categories -- 11. The Parallelism of Inner and Outer Sense -- 12. The Subject of Experience -- 13. How Representations Make Objects Possible -- 14. Objects and Empirical Realism -- 15. The Idealistic Understanding of Kant's Theoretical Philosophy
Includes bibliographical references (pages 183-198) and index
Keywords: Kant, Immanuel, -- 1724-1804.; Knowledge, Theory of; Causation; Reason